Shaping Modern Society: The Transformative Role of Information Technology - Geofrey Nyabuto (International Journal of Advanced Science and Computer Applications, 2026)
Information Technology (IT), a key field in computing, focuses on the creation, collection, processing, storage, and retrieval of information through digital systems. Over the past three decades, IT has profoundly transformed societal activities, reshaping how individuals and organizations operate. This paper examines the dual impact of IT, highlighting its positive contributions to societal growth and well-being while also addressing the challenges and negative consequences it has introduced. By exploring both perspectives, this review provides a comprehensive understanding of IT's role in shaping modern society